Autism spectrum disorder in the criminal justice system : a guide to understanding suspects, defendants and offenders with autism - Allely, Clare S. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book focuses on autism spectrum disorder (ASD) in the criminal justice system. Rather than being the perpetrators of offending, individuals with ASD are more likely to be the victim of crime. However, there is nevertheless a small subset of individuals with ASD who do offend, and this book provides an in-depth understanding of how certain features of ASD may provide the context of vulnerability to engaging in a number of types of offending behaviours. Chapters focus on arson or fire-setting; cybercrime (e.g., hacking); online sexual offending such as the viewing of indecent child imagery; offline sexual offending; violent crime; stalking; terroristic behaviour (including radicalisation and extremism); bestiality or zoophilia and also extreme violence such as mass shooting and serial homicide. This book also outlines the ways in which a defendant with ASD may present in court and how they may exhibit behaviour which could be misinterpreted and perceived negatively leading to an unfair trial. Lastly, it discusses the need to identify the impact that ASD can have on the capacity to form the requisite criminal intent and offer appropriate court adaptations to support them during court proceedings. This book is ideal for criminal defense lawyers and practitioners in psychology, psychiatry, and social work as well as policy makers and reformers"--
What is autism spectrum disorder (ASD)? -- ASD and offending behaviour : why it is important to recognise how ASD symptomology can provide the context of vulnerability for engaging in offending and important considerations when interviewed by police and other criminal justice professionals -- Risk assessment : ASD and issues with current standardised risk assessment -- Prevalence of ASD in forensic settings -- Psychiatric co-morbidity in ASD -- ASD in the courtroom : why it is important to recognise this disorder in defendants -- ASD and arson -- ASD and sexual offences (offline and online) -- ASD and cybercrime -- ASD and violent offending -- ASD and radicalisation and extremism -- ASD and extreme violence -- ASD and stalking -- ASD in the prison environment -- Conclusions and recommendations.
OCLC-licensed vendor bibliographic record.
Keywords: Offenders with mental disabilities; Autism spectrum disorders; Criminal justice, Administration of; LAW / Criminal Law / General; PSYCHOLOGY / General; PSYCHOLOGY / Forensic Psychology